Photocuring printing ink, preparation method thereof, polymer material and application thereof

Polymer materials prepared by photopolymerization printing ink have solved the problems of non-degradability and insufficient biocompatibility of existing implant materials, achieving high-precision molding and excellent mechanical properties, and are suitable for medical devices such as vascular interventional devices.

CN121021748APending Publication Date: 2025-11-28LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511345868.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-19
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing implant materials for the treatment of vascular diseases suffer from problems such as non-degradability, long-term implantation complications, incompatibility of mechanical properties with vascular tissue, and insufficient biocompatibility.

Method used

Polymer materials are prepared using photopolymer printing ink. By combining the comonomers 2-hydroxyethyl acrylate and N-vinylcaprolactam with tannic acid, a polymer with degradability, good biocompatibility and mechanical properties is formed. High-precision molding is achieved using photopolymer printing technology.

Benefits of technology

Polymer materials possess excellent mechanical properties, shape memory properties, and biocompatibility, meeting the safety requirements of medical implants. They are suitable for vascular interventional devices, flexible sensors, and temperature control valves, reducing the risk of mechanical damage and complications after implantation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121021748A_ABST
    Figure CN121021748A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of printing materials, and particularly relates to photocuring printing ink, a preparation method thereof, a polymer material and application thereof. The photocuring printing ink provided by the invention is prepared from acrylic acid-2-hydroxyethyl ester, N-vinyl caprolactam and tannic acid. According to the invention, a polymer formed by photocuring after printing by using photocuring printing ink is utilized, and hydrophilicity is provided by acrylic acid-2-hydroxyethyl ester; the polymer material is endowed with shape memory performance by utilizing the temperature sensitivity of N-vinyl caprolactam, and the near body temperature phase change response can be regulated and controlled; by introducing tannic acid, the adaptability and biocompatibility of a polymer material and the mechanical property of a human body structure are realized, and mechanical injury after implantation is avoided; meanwhile, through tannic acid, the antibacterial and anti-inflammatory characteristics of the polymer can be improved. Under the ternary synergistic effect of the acrylic acid-2-hydroxyethyl ester, the N-vinyl caprolactam and the tannic acid, the problems of insufficient biocompatibility and mechanical mismatch of the existing implant are solved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of printing materials, and particularly relates to a photocuring printing ink, a preparation method thereof, a polymer material and application thereof. BACKGROUND

[0002] Vascular diseases can cause problems in blood circulation, directly affecting the oxygen supply of organs and tissues in the body; if the oxygen supply is insufficient, it can cause local or systemic discomfort such as fatigue, dizziness, indigestion, chest tightness, etc.; among them, atherosclerosis is the most important pathological basis. With the development of medical technology, the treatment mode of vascular diseases has gradually changed from traditional open surgery to minimally invasive treatment, and endovascular interventional therapy has become the main treatment method for peripheral vascular diseases. However, the existing implant materials (such as shape memory metals) have many limitations, such as non-degradability, long-term implantation complications (such as filter thrombosis, filter migration), mechanical properties and blood vessel tissue mismatch, and insufficient biocompatibility. SUMMARY

[0003] Therefore, the application provides a photocuring printing ink, a preparation method thereof, a polymer material and application thereof. The polymer provided by the application has good biocompatibility and mechanical properties, and is degradable, and can be implanted into the human body as an interventional instrument.

[0004] To solve the above technical problems, the application provides a photocuring printing ink, which comprises the following components in parts by mass: 7-13 parts of a comonomer; 0.3-1.5 parts of tannic acid; 0.05-0.3 parts of a photoinitiator; 1-3.5 parts of a solvent; The comonomer comprises 2-hydroxyethyl acrylate and N-vinyl caprolactam, and the mass ratio of the 2-hydroxyethyl acrylate and the N-vinyl caprolactam is 4-7:3-6; The solvent comprises water and ethanol, and the mass ratio of the water and the ethanol is 1-2.5:0.3-1.

[0005] Preferably, the photoinitiator comprises diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide or 2,4,6-trimethylbenzoyl-di(p-tolyl) phosphine oxide.

[0006] The application further provides a preparation method of the photocuring printing ink described in the above technical solution, comprising the following steps: The 2-hydroxyethyl acrylate, the N-vinyl caprolactam and the photoinitiator are first mixed to obtain a premix; The tannic acid and the solvent are secondly mixed to obtain a tannic acid solution; The premixed solution and the tannic acid solution are mixed to obtain the photocuring printing ink.

[0007] Preferably, before the first mixing, the 2-hydroxyethyl acrylate is subjected to chromatographic purification, and the chromatographic purification uses a chromatographic column comprising an alkaline aluminum oxide column.

[0008] Preferably, the first mixing is performed under magnetic stirring, and the time of the magnetic stirring is 25-35 min.

[0009] Preferably, the second mixing is performed under vortex oscillation, the rotation speed of the vortex oscillation is 2400-2600 rpm, and the time of the vortex oscillation is 0.8-1.2 min.

[0010] Preferably, the third mixing is performed under vortex oscillation, the rotation speed of the vortex oscillation is 2400-2600 rpm, and the time of the vortex oscillation is 2.5-3.5 min.

[0011] The application further provides a polymer material, comprising a copolymer and tannic acid connected to the copolymer by hydrogen bonds. The polymerized monomers of the copolymer are 2-hydroxyethyl acrylate and N-vinyl caprolactam.

[0012] Preferably, the preparation method of the polymer material comprises method 1 and method 2. The method 1 comprises the following steps: placing the photocuring printing ink in a mold for photocuring to obtain the polymer material; the radiation intensity of the photocuring is 28-32 mW / cm 2 , and the time is 4-6 min. The method 2 comprises the following steps: photocuring printing the photocuring printing ink to obtain the polymer material; the light source used for the photocuring printing comprises ultraviolet light, and the wavelength of the ultraviolet light is 365-400 nm; the radiation intensity of the photocuring printing is 14-20 mW / cm 2 , and the time is 0.4-0.5 min.

[0013] The application further provides an application of the polymer material in the preparation of a vascular interventional instrument, a flexible sensor or a temperature control valve.

[0014] The present application provides a photocuring printing ink, comprising 2-hydroxyethyl acrylate, N-vinyl caprolactam and tannic acid. The present application uses the polymer formed by photocuring after printing the photocuring printing ink, and the 2-hydroxyethyl acrylate (HEA) provides the hydrophilicity of the polymer; the temperature sensitivity of the N-vinyl caprolactam (NVCL) is used to endow the polymer with shape memory performance, and the near-body temperature phase change response can be regulated; by introducing the tannic acid, the adaptability of the polymer material to the mechanical properties of the human body structure and the biocompatibility can be realized, and mechanical damage after implantation can be avoided; at the same time, the tannic acid can improve the antibacterial and anti-inflammatory properties of the polymer. The present application solves the problems of insufficient biocompatibility and mechanical mismatch of the existing implant under the synergistic effect of 2-hydroxyethyl acrylate, N-vinyl caprolactam and tannic acid. The present application uses a mixed solvent of water and ethanol as the solvent of the printing ink to solve the dispersion problem of TA in the hydrophobic system, and to ensure the stability and printing precision of the printing ink.

[0015] The polymer material provided by the present application has a standard verified hemolysis rate of less than or equal to 5%, a cell survival rate of greater than 90%, and meets the safety requirements of medical implants. The polymer material provided by the present application has excellent mechanical properties, a phase transition temperature close to that of the human body, excellent shape memory performance and biocompatibility, and can be applied to complex environments. BRIEF DESCRIPTION OF DRAWINGS

[0016] Figure 1 A schematic diagram for preparing a polymer material using 2-hydroxyethyl acrylate, N-vinyl caprolactam and tannic acid as raw materials; Figure 2 A DSC curve of the polymer prepared in Example 1 and Comparative Example 1; Figure 3 Stress-strain curves of the polymer prepared in Examples 1-3 and Comparative Example 1 before and after swelling; Figure 4 A compression strength columnar comparison graph of the polymer prepared in Examples 1-3 and Comparative Example 1 before and after swelling; Figure 5 A shape memory cycle curve of the polymer prepared in Example 1; Figure 6 Swelling curves of the polymer prepared in Examples 1-3 and Comparative Example 1; Figure 7 A swelling rate columnar comparison graph of the polymer material prepared in Examples 1-3 and Comparative Example 1 after incubation for 24 hours; Figure 8 A water contact angle columnar comparison graph of the polymer material prepared in Examples 1-3 and Comparative Example 1; Figure 9A columnar comparison chart of hemolysis rates of the polymer materials prepared for Examples 1~3 and Comparative Example 1. DETAILED DESCRIPTION

[0017] The present application provides a photocuring printing ink, comprising the following components by mass fraction: a comonomer 7~13 parts; tannic acid 0.3~1.5 parts; a photoinitiator 0.05~0.3 parts; a solvent 1~3.5 parts; The comonomer comprises 2-hydroxyethyl acrylate and N-vinyl caprolactam, and the mass ratio of the 2-hydroxyethyl acrylate and N-vinyl caprolactam is 4~7:3~6; The solvent comprises water and ethanol, and the mass ratio of the water and ethanol is 1~2.5:0.3~1.

[0018] The photocuring printing ink provided by the present application comprises 7~13 parts of a comonomer by mass fraction, which can be specifically 8 parts, 9 parts, 10 parts, 11 parts or 12 parts; the comonomer comprises 2-hydroxyethyl acrylate and N-vinyl caprolactam, and the mass ratio of the 2-hydroxyethyl acrylate and N-vinyl caprolactam is 4~7:3~6, which can be 5~6:4~5, and can be specifically 1:1.

[0019] The photocuring printing ink provided by the present application comprises 0.3~1.5 parts of tannic acid by mass fraction of the comonomer, which can be 0.4 parts, 0.5 parts, 0.7 parts, 1 part, 1.3 parts or 1.4 parts. The present application can improve the antibacterial property of the polymer material and inhibit its swelling by introducing tannic acid.

[0020] The photocuring printing ink provided by the present application comprises 0.05~0.3 parts of a photoinitiator by mass fraction of the comonomer, which can be 0.08 parts, 0.1 parts, 0.15 parts or 0.2 parts. As a specific embodiment of the present application, the photoinitiator can comprise diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (TPO) or 2,4,6-trimethylbenzoyl-di(p-tolyl) phosphine oxide.

[0021] The photocuring printing ink provided by the present application comprises 1-3.5 parts of solvent, which can be 1.2 parts, 1.72 parts, 2 parts, 2.4 parts, 3 parts, 3.2 parts or 3.4 parts, based on the mass fraction of the comonomer. As a specific embodiment of the present application, the solvent comprises water and ethanol, the water can be deionized water, and the ethanol can be anhydrous ethanol; the mass ratio of the water and the ethanol is 1-2.5:0.3-1, which can be 1.5-2:0.5; in the embodiments of the present application, the mass ratio of the water and the ethanol is 2:1, 3:1, 3.1:1 or 3.2:1. The use of the mixed solvent of water and ethanol as the solvent in the present application can improve the dispersibility of tannic acid in the system.

[0022] The photocuring printing ink provided by the present application can be stored for more than 72 hours under light-proof conditions.

[0023] The present application also provides a preparation method of the photocuring printing ink described in the above technical solution, which comprises the following steps: The acrylic acid-2-hydroxyethyl ester, N-vinyl caprolactam and the photoinitiator are first mixed to obtain a premix solution; The tannic acid and the solvent are secondly mixed to obtain a tannic acid solution; The premix solution and the tannic acid solution are thirdly mixed to obtain the photocuring printing ink.

[0024] The acrylic acid-2-hydroxyethyl ester, N-vinyl caprolactam and the photoinitiator are first mixed to obtain a premix solution. As a specific embodiment of the present application, the first mixing can further comprise chromatographic purification of the acrylic acid-2-hydroxyethyl ester, and the chromatographic purification uses a chromatographic column comprising an alkaline alumina column. The chromatographic purification can remove impurities such as polymerization inhibitors in the acrylic acid-2-hydroxyethyl ester.

[0025] As a specific embodiment of the present application, the first mixing can be carried out under the condition of magnetic stirring, and the time of the magnetic stirring can be 25-35 min, specifically 30 min; the magnetic stirring is carried out under light-proof conditions; the premix solution is a light yellow transparent liquid (prepolymer of hydrogel).

[0026] The tannic acid and the solvent are secondly mixed to obtain a tannic acid solution. As a specific embodiment of the present application, the second mixing can be carried out under the condition of vortex oscillation, and the rotation speed of the vortex oscillation can be 2400-2600 rpm, specifically 2500 rpm; the time of the vortex oscillation can be 0.8-1.2 min, specifically 1 min.

[0027] After the premixing solution and the tannic acid solution are obtained, the premixing solution and the tannic acid solution are mixed to obtain the photocuring printing ink. As a specific embodiment of the present application, the third mixing can be carried out under the condition of vortex oscillation, the rotation speed of the vortex oscillation can be 2400-2600 rpm, and can be specifically 2500 rpm; the vortex oscillation time can be 2.5-3.5 min, and can be specifically 3 min; and the third mixing is carried out in the light-proof condition.

[0028] The present application also provides a polymer material comprising a copolymer and tannic acid connected to the copolymer by hydrogen bond. The polymerized monomers of the copolymer are 2-hydroxyethyl acrylate and N-vinyl caprolactam.

[0029] As a specific embodiment of the present application, the preparation method of the polymer material can comprise method 1 and method 2.

[0030] In the present application, the method 1 can comprise the following steps: placing the photocuring printing ink in a mold for photocuring to obtain the polymer material. As a specific embodiment of the present application, the mold can be a polytetrafluoroethylene mold, and the present application does not have special requirements for the size and shape of the mold, which can be designed according to the shape and size of the required polymer material. As a specific embodiment of the present application, the photocuring printing ink placed in the mold can be further subjected to the following steps before photocuring: standing for 9-11 min, and can be specifically standing for 10 min; the radiation intensity of the photocuring can be 28-32 mW / cm 2 , and can be specifically 30 mW / cm 2 ; and the photocuring time can be 4-6 min, and can be specifically 5 min.

[0031] In the present application, the method 2 can comprise the following steps: photocuring printing the photocuring printing ink to obtain the polymer material. As a specific embodiment of the present application, the photocuring printing can be photocuring 4D printing; the light source for the photocuring printing comprises ultraviolet light, the wavelength of the ultraviolet light can be 365-400 nm, and can be specifically 365 nm or 400 nm; and the radiation intensity of the photocuring printing can be 14-20 mW / cm 2 , and can be specifically 14 mW / cm 2 , 15 mW / cm 2 , 16 mW / cm 2 , 17 mW / cm 2 , 18 mW / cm 2 , 19 mW / cm 2 , or 20 mW / cm 2The light-cured printing time can be 0.4-0.5 min. The present application realizes high-precision personalized forming through 4D printing technology.

[0032] The present application takes acrylic acid-2-hydroxyethyl ester (HEA) and N-vinyl caprolactam (NVCL) as the main material, and combines the functional modification of tannic acid (TA), aiming to improve biocompatibility, mechanical properties and intelligent functions. HEA provides hydrophilic properties to prevent thrombosis, NVCL gives the material temperature-sensitive shape memory performance, and TA enhances the antibacterial and anti-inflammatory properties and reduces the swelling rate, optimizing the mechanical properties. Through 4D printing technology, high-precision forming is realized to meet the needs of personalized medical treatment. Experimental results show that the polymer material provided by the present application has excellent mechanical properties (such as tensile strength and elongation at break), shape memory performance (both shape fixation rate and recovery rate are more than 90%), hydrophilic properties and biocompatibility (such as low hemolysis rate).

[0033] Figure 1 A schematic diagram for preparing a polymer material from acrylic acid-2-hydroxyethyl ester, N-vinyl caprolactam and tannic acid.

[0034] In the curing process, the present application forms a HEA-NVCL copolymer network and embeds a cross-linked structure of tannic acid molecules in the copolymer network. FT-IR spectrum confirms that the phenolic hydroxyl group of TA forms a hydrogen bond with the carbonyl group of NVCL, improving the cross-linking degree and effectively inhibiting the swelling of the polymer material; the dry compressive strength of the polymer material can be 23-49 MPa, and can also be 36.4-48.86 MPa; the dry compressive strain rate of the polymer material is greater than 87%, and can be 90%; the hydrophilic performance of the polymer material is that the water contact angle is <90°, the swelling rate in deionized water at room temperature for 24 h can be 24-40%, and can also be 30-39%; the biological safety meets the hemolysis rate far below the international standard limit, and realizes a shape recovery rate of more than 90% in a 37℃ physiological environment.

[0035] The present application also provides the use of the polymer material in the preparation of a vascular interventional instrument, a flexible sensor or a temperature control valve. As a specific embodiment of the present application, the vascular interventional instrument can include a vascular stent. The present application can utilize the near-body-temperature phase change characteristics of the polymer material to realize the self-expanding function after implantation; the polymer material can be used as a myocardial repair patch in tissue engineering, maintaining mechanical stability with low swelling rate; and intelligent embolization microspheres can be customized through 4D printing, combined with the >99% bacteriostatic rate of TA to reduce the risk of infection. In addition, the polymer material can be used in the preparation of flexible sensors and microfluidic temperature control valves in the industrial field.

[0036] In order to further illustrate the present application, the technical solutions provided by the present application are described in detail below in conjunction with examples, but they should not be understood as limiting the scope of protection of the present application.

[0037] The sources of the materials in the examples: 2-hydroxyethyl acrylate was purchased from Anhui Zesheng Technology Co., Ltd., N-acetyl caprolactam was purchased from Anhui Zesheng Technology Co., Ltd., tannic acid was purchased from Anhui Zesheng Technology Co., Ltd., diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide was purchased from Anhui Zesheng Technology Co., Ltd., and water was self-made deionized water.

[0038] Example 1 The 2-hydroxyethyl acrylate was purified by basic alumina packed column chromatography, 1.65 g of the purified 2-hydroxyethyl acrylate, 1.35 g of N-vinyl caprolactam and 30 mg of diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide were added to a light-proof bottle for 30 min of magnetic stirring to obtain a light yellow transparent premix (hydrogel prepolymer); 300 mg of tannic acid, 150 mg of anhydrous ethanol and 450 mg of deionized water were vortexed at 2500 rpm for 1 min to obtain a tannic acid solution; The tannic acid solution and the premix were vortexed at a speed of 2500 rpm for 3 min to obtain a light-cured printing ink.

[0039] The light-cured printing ink was placed in a polytetrafluoroethylene mold and left to stand for 10 min, then a free radical polymerization reaction was initiated under the irradiation of ultraviolet light (25℃, 365 nm, 30 mW / cm²) for 5 min of light curing to obtain a polymer material, which was recorded as HEN5.5-TA10.

[0040] Example 2 The light-cured printing ink was prepared according to the method of Example 1, except that the mass of tannic acid was 210 mg, the mass of anhydrous ethanol was 105 mg, and the mass of deionized water was 325 mg.

[0041] The polymer material was prepared according to the method of Example 1, and the prepared polymer material was recorded as HEN5.5-TA7.

[0042] Example 3 The light-cured printing ink was prepared according to the method of Example 1, except that the mass of tannic acid was 150 mg, the mass of anhydrous ethanol was 75 mg, and the mass of deionized water was 225 mg.

[0043] The polymer material was prepared according to the method of Example 1, and the prepared polymer material was recorded as HEN5.5-TA5.

[0044] Comparative Example 1 The 2-hydroxyethyl acrylate was purified by basic alumina packing column chromatography, 1.65 g of purified 2-hydroxyethyl acrylate, 1.35 g of N-vinyl caprolactam and 30 mg of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide were added into a light-proof bottle and uniformly stirred by magnetic stirring for 30 min, and then placed in a polytetrafluoroethylene mold for 10 min; under the irradiation of ultraviolet light (25°C, 405 nm, 30 mW / cm²), a free radical polymerization reaction was initiated, and the light curing was carried out for 5 min to obtain a polymer material, which was recorded as HEN5.5.

[0045] Test Example 1 1. Thermodynamic property test: The thermal mechanical properties of the copolymer were characterized by using a differential scanning calorimeter (DMA 850 TA) to obtain the transition temperature (Tr) of the polymer, and then the dynamic mechanical analyzer was used to verify the transition temperature. The differential scanning calorimetry (DSC) experiment was carried out under nitrogen atmosphere, the sample was heated from room temperature to 150°C to eliminate thermal history, then cooled to room temperature and cooled to-50°C, the verification experiment was carried out in tension mode, the oscillation frequency was set to 1 Hz, the test temperature range was 0°C to 60°C, and the heating rate was 10°C / min. To ensure the repeatability and reliability of the experimental data, each sample was tested with at least three or more samples, and the obtained data was statistically analyzed, and the results are shown in Table 1; the DSC curves of Example 1 and Comparative Example 1 obtained are shown in Figure 2 .

[0046] Table 1 Transition temperature of the polymer material prepared in Example 1 and Comparative Example 1

[0047] From Table 1 and Figure 2 It can be seen that the introduction of tannic acid can significantly reduce the transition temperature of the hydrogel, and the transition temperature can be controlled by adjusting the content of tannic acid in the system.

[0048] 2. Compression property test: The mechanical properties of the polymer materials were tested at room temperature (25°C) using a universal testing machine (Shimadzu AD-X 5000 N). The samples used for testing were designed in accordance with the international standard (BS EN ISO 527-2:1996) and printed into a cylindrical shape using a 3D printer for uniaxial compression experiments. The compression rate was 5 mm / min, and the maximum compression value was set to 90%. The compression strength and compression rate were calculated. The swollen samples were obtained by immersing the standard samples in deionized water for 24 h, and the same method was used for the compression test. The final results of the compression test were the average of three parallel samples, and the results are listed in Table 2; the stress-strain curves obtained are shown in Figure 3 .

[0049] Table 2 Strength and elongation at break of the polymer materials prepared in Examples 1-3 and Comparative Example 1

[0050] According to Table 2, a columnar comparison chart of the compression strength of the polymer materials before and after swelling was drawn, as shown in Figure 4 .

[0051] It can be seen from Table 2 and Figure 3 that Comparative Example 1 without the introduction of tannic acid has a sharp decrease in mechanical properties after swelling, showing obvious mechanical mismatch; while Examples 1-3 with the introduction of tannic acid can significantly improve the mechanical retention after swelling, among which Example 2 has the best performance, showing higher compression strength after swelling and stable strain recovery ability. This indicates that tannic acid enhances the structural stability in the polymer network through hydrogen bonding, reduces the strength decay caused by hydration, and thus improves the overall mechanical properties of the material.

[0052] It can be seen from Table 2 and Figure 4 that Comparative Example 1 has a relatively high compression strength before swelling, but it decreases significantly after swelling, showing insufficient mechanical stability and obvious hydration fragility. While Examples 1-3 have relatively small differences in strength before and after swelling, and the compression rate is always maintained at a high level, indicating that the introduction of tannic acid can effectively enhance the mechanical retention of the material in a wet environment. Among them, Example 2 performs the best, balancing the high compression strength after swelling and good compression rate, proving that an appropriate amount of tannic acid can enhance the structural stability of the polymer network through hydrogen bonding crosslinking, thereby optimizing its biological adaptability and durability.

[0053] 3. Shape memory ability characterization: A dynamic mechanical analyzer (DMA) was used to perform cyclic thermal mechanical experiments on the polymer material in tensile mode to quantitatively evaluate its shape memory effect. The process was as follows: 1. Shape fixation: the sample was first stretched to about 30% of the breaking elongation at 60°C. 2. Temperature reduction fixation: quickly cooled to 0°C to fix the temporary shape. 3. Shape recovery: the sample was heated at a rate of 10°C / min, and the shape recovery was recorded. The experiment evaluated the shape memory performance of the material by calculating the shape fixation rate (Rf) and the shape recovery rate (Rr); the results are listed in Table 3, and the shape memory cycle curve of the polymer prepared in Example 1 is shown in Figure 5 .

[0054] Table 3 Shape fixation rate and shape recovery rate of the polymer materials prepared in Example 1 and Comparative Example 1

[0055] As can be seen from Table 3 and Figure 5 , both Example 1 and Comparative Example 1 exhibit high shape fixation rates (close to 100%) and shape recovery rates (>90%), indicating that the prepared polymers both have good shape memory performance. However, the transition temperature of Comparative Example 1 is high (54.4°C), exceeding the human body temperature range, and is not suitable for in vivo implantation; in contrast, the transition temperature of Example 1 is reduced to 42.8°C, and the shape recovery can be achieved near the human body temperature, which is more suitable for the use requirements of clinical implant materials. Therefore, the introduction of tannic acid not only endows the material with good biocompatibility and mechanical retention, but also adjusts the phase transition temperature to the vicinity of the body temperature range, thereby making it have practical application value.

[0056] 4. Hydrophilic performance: A contact angle measuring instrument (DSA100-KRUSS-Germany) was used to measure the water contact angle of the polymer material to evaluate its hydrophilic performance. The steps were as follows: first, the polymer material was made into a thin film sample and fixed on a glass slide, and the surface was ensured to be smooth and flat; then 20 μL of deionized water was added on the surface of the thin film, and the tangent angle formed by the water droplet and the surface of the thin film was measured and recorded, and the hydrophilic performance of the material was evaluated, and each sample was measured at least 3 times, and the results are listed in Table 4.

[0057] Different shapes of the polymer material in a stable state were immersed in 37°C phosphate buffered physiological saline (PBS) and placed in a shaking incubator for incubation. After 1 h, 2 h, 4 h, 8 h, 12 h, and 24 h, respectively, the excess liquid on the surface was gently wiped off with filter paper, and the mass of each sample was recorded. To ensure the reliability of the experimental results, each group of samples was measured at least three times at each time node, and the average swelling rate was calculated, and the results are listed in Table 4; the swelling curve obtained is as followsFigure 6 As shown.

[0058] Table 4 Water contact angle and swelling ratio of the polymer materials prepared in Examples 1-3 and Comparative Example 1

[0059] A bar chart comparison of the swelling ratio of the polymer materials prepared in Examples 1-3 and Comparative Example 1 after incubation for 24 h is drawn according to Table 4, as shown in Figure 7 A bar chart comparison of the water contact angle of the polymer materials prepared in Examples 1-3 and Comparative Example 1 is drawn according to Table 4, as shown in Figure 8

[0060] It can be seen from Table 4 and Figure 6 , 7 , 8 that the surface of Comparative Example 1 is hydrophobic (contact angle 96.68°) due to the lack of hydrogen bond crosslinking of tannic acid, and it exhibits a swelling ratio as high as 61.7% in the swelling experiment, indicating that the material is unstable in the body fluid environment. The contact angles of Examples 1-3 are all lower than 90°, changing from hydrophobic to hydrophilic, which significantly improves the blood compatibility; the swelling ratios of Examples 1-3 after incubation for 24 h are also controlled within the range of 24-40%, which is significantly lower than that of Comparative Example 1, and tends to be stable after 12 h. Among them, the swelling ratio of Example 2 after incubation for 24 h is the lowest (24.5%), and the comprehensive performance is the best. This indicates that the introduction of tannic acid not only improves the hydrophilicity of the material, but also inhibits excessive water absorption and swelling through hydrogen bond interaction, and improves the mechanical stability and biological adaptability of the material.

[0061] 5. Hemolysis performance: In this study, in vitro hemolysis experiment was used to evaluate the blood compatibility of the material. The specific operation process is as follows: (1) collect 3 mL of fresh venous blood in an EDTA anticoagulant tube, and obtain the red blood cell precipitate by centrifugation at 1500 r / min for 10 min; (2) weigh 1 mL of bottom red blood cells, and dilute to 50 mL with normal saline to prepare a red blood cell suspension; (3) mix the circular sample with 1.5 mL of diluted blood in a sterile centrifuge tube, and incubate in a constant temperature incubator (amplitude 15 mm, frequency 60 rpm) at 37°C for 120 min; (4) set up a double-phase control group: the positive control is diluted in ultrapure water, and the negative control is diluted in normal saline; (5) after secondary centrifugation at 1500 r / min for 10 min, the supernatant is detected in a UV-visible spectrophotometer at 545 nm, and the hemolysis rate is calculated according to Formula 1, and the results are listed in Table 5. Hemolysis rate (%) = (sample group absorbance-negative control group absorbance) / (positive control group absorbance-negative control group absorbance) x 100% Formula 1.

[0062] ​Table 5 Hemolysis rate of the polymer materials prepared in Examples 1-3 and Comparative Example 1

[0063] A column contrast chart of the hemolysis rate of the polymer materials prepared in Examples 1-3 and Comparative Example 1 was drawn according to Table 5, as shown in Figure 9 .

[0064] It can be seen from Table 5 and Figure 9 that the hemolysis rates of Examples 1-3 and Comparative Example 1 are all far below the international standard limit of 5%, indicating that the polymer materials have good blood compatibility. Among them, the examples with the addition of tannic acid perform better, especially Example 3, whose hemolysis rates are 0.06% and 0.02% respectively, almost causing no hemolysis reaction. This shows that the introduction of tannic acid not only endows the material with good mechanical stability and anti-swelling performance, but also further improves the blood compatibility, which can effectively reduce the risk of hemolysis or thrombosis after implantation.

[0065] Conclusion: Compared with Comparative Example 1 without the addition of tannic acid, after the addition of tannic acid, the decrease of the mechanical properties of the material after swelling is obviously improved, and the transition temperature is closer to the body temperature, the material changes from the previous hydrophobic state to hydrophilic state, and the swelling rate decreases obviously.

[0066] Although the above examples have made a detailed description of the present application, it is only a part of the embodiments of the present application, not all the embodiments, and people can also obtain other embodiments according to the present embodiments without creativity, which all belong to the protection scope of the present application.

Claims

1. A photocurable printing ink, characterized in that, The components include the following parts by weight: 7-13 parts of copolymer monomer; Tannic acid 0.3~1.5 parts; Photoinitiator 0.05~0.3 parts; Solvent: 1-3.5 parts; The comonomers include 2-hydroxyethyl acrylate and N-vinylcaprolactam, wherein the mass ratio of 2-hydroxyethyl acrylate to N-vinylcaprolactam is 4~7:3~6; The solvent includes water and ethanol, and the mass ratio of water to ethanol is 1~2.5:0.3~1.

2. The photocurable printing ink according to claim 1, characterized in that, The photoinitiator includes diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide or 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide.

3. The method for preparing the photocurable printing ink according to claim 1 or 2, characterized in that, Includes the following steps: 2-Hydroxyethyl acrylate, N-vinylcaprolactam and photoinitiator were first mixed to obtain a premix; A second mixing of tannic acid and solvent yields a tannic acid solution. The premixed liquid and tannic acid solution are mixed a third time to obtain the photocurable printing ink.

4. The preparation method according to claim 3, characterized in that, The first mixing process further includes: purifying the 2-hydroxyethyl acrylate by chromatography, wherein the chromatography column used for purification includes an alkaline alumina column.

5. The preparation method according to claim 3 or 4, characterized in that, The first mixing is carried out under magnetic stirring conditions for 25-35 minutes.

6. The preparation method according to claim 3, characterized in that, The second mixing is carried out under vortex oscillation conditions, wherein the vortex oscillation speed is 2400~2600 rpm and the vortex oscillation time is 0.8~1.2 min.

7. The preparation method according to claim 3, characterized in that, The third mixing is carried out under vortex oscillation conditions, the vortex oscillation speed is 2400~2600 rpm, and the vortex oscillation time is 2.5~3.5 min.

8. A polymer material, characterized in that, Includes copolymers and tannic acid linked to the copolymers by hydrogen bonds; The copolymer's monomers are 2-hydroxyethyl acrylate and N-vinylcaprolactam.

9. The polymer material according to claim 8, characterized in that, The preparation method of the polymer material includes method 1 and method 2; Method 1 includes the following steps: placing the photocurable printing ink in a mold for photocuring to obtain the polymer material; the radiation intensity of the photocuring is 28~32mW / cm². 2 The time is 4-6 minutes; Method 2 includes the following steps: performing photocurable printing on photocurable ink to obtain the polymer material; the light source for photocurable printing includes ultraviolet light with a wavelength of 365~400nm; the radiation intensity of the photocurable printing is 14~20 mW / cm². 2 The time is 0.4~0.5 min.

10. The use of the polymer material of claim 8 or 9 in the preparation of vascular interventional devices, flexible sensors or temperature control valves.